PERAN KEPEMIMPINAN VISIONER KEPALA SEKOLAH DALAM IMPLEMENTASI MANAJEMEN PENDIDIKAN MODERN - Isny Lellya (JIP: Jurnal Ilmu Pendidikan, 2025)
This study aims to examine the role of visionary leadership of school principals in the implementation of modern education management through a literature review approach. In the era of globalisation and technological advancement, school principals are required to have a clear vision, be innovative, and be able to inspire the entire school community in facing the challenges of 21st-century education. This study identifies that visionary school principals play a crucial role in formulating the school's vision and mission, building a collaborative organisational culture, promoting innovative learning, and optimising resource management. Visionary leadership also impacts the improvement of teacher professionalism, parent participation, and community involvement in supporting school programmes. However, the success of modern educational management implementation is greatly influenced by resource support, active participation of the entire school community, and the principal's ability to overcome challenges of change. The findings of this study confirm that visionary leadership of school principals is the key to creating adaptive, innovative, and competitive schools in the modern era of education.